Waist circumference measurement site does not affect relationships with visceral adiposity and cardiometabolic risk factors in children. Issue 3 (21st November 2012) - Harrington, D. M.; Staiano, A. E.; Broyles, S. T.; Gupta, A. K.; Katzmarzyk, P. T.
Summary What is already known about this subject A number of anatomic sites are used for the measurement of waist circumference. A number of studies have documented differences in the absolute values of waist circumference measurements across these common sites in adults. It is unclear whether waist circumference measurement site alters the relationship with abdominal adiposity and cardiometabolic risk factors in children. What this study adds The absolute values of waist circumference at four anatomic locations (minimal, midway, iliac, umbilicus) differed and this affected prevalence of high (≥90th percentile) waist circumference. The relationships between waist circumference values at four anatomic locations and both depot‐specific adiposity and cardiometabolic risk factors were similar across race and sex groups. Background Different waist circumference (WC) measurement sites are used in clinical and epidemiological settings. Objectives To examine differences in WC measurement at four anatomic sites and how each WC measurement relates to visceral adipose tissue (VAT) and cardiometabolic risk factors in children. Methods A total of 371 white and African–American children aged 5 to 18 years had WC measured at four sites: minimal waist, midpoint between the iliac crest and the lowest rib, superior border of the iliac crest and the umbilicus. Abdominal VAT was measured using magnetic resonance imaging and cardiometabolic risk factors were defined using National Heart, Lung and Blood Institute guidelines. Relationships between WC sites and VAT and risk factors were explored in each race‐by‐sex group. Results All WC sites were highly correlated (r = 0.97 to 0.99). Differences in absolute mean WC values existed in all race‐by‐sex groups, and this affected the prevalence of high WC (≥90th percentile). Values were lowest for minimal waist and highest for umbilicus. Age‐controlled partial correlations between WC and logVAT VAT were 0.81–0.89 (all P < 0.001) and between WC and cardiometabolic risk factors were −0.24 to ‐0.41 and 0.19 to 0.52 (all P < 0.05). Conclusions While the absolute values of WC at four anatomic locations differed, the relationships between WC values and both VAT and cardiometabolic risk factors were similar within all race‐by‐sex groups.